PENGELOLAAN BUMDES DI PANGKALAN TAMPOI KECAMATAN KERUMUTAN KABUPATEN PELALAWAN - M. Sabda Abdyagra Abdyagra; Adlin ' (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2023)
This research was carried out with the aim of knowing the management of Pangkalan Tampoi Village-Owned Enterprises, Kerumutan District, Pelalawan Regency in 2023, which was reviewed based on the indicators that are the basis for the growth of Pangkalan Tampoi Village. Village-Owned Enterprises are institutions that are managed directly by the community and also the Village Government in an effort to strengthen the Village economy. This research aims to find out the process of managing Village-Owned Enterprises in Pangkalan Tampoi Village, Kerumutan District, Pelalawan District. The research approach used is descriptive qualitative. By using this technique, data collection begins by conducting interviews with informants who have the potential to provide accurate information about the management process of Pangkalan Tampoi Village-Owned Enterprises, and also through interviews and documenting the results of BUMDes management. The theory used in this research is Sutoro Eko, which contains several indicators, namely Leadership, Managerial and Governance (KMT), Business Scale and Reach, Local Emancipation, Cooperation, Village Traditions. The research results show that BUMDes Pangkalan Tampoi has been established for 3 years, BUMDes Pangkalan Tampoi in its management is still in the developing stage. Currently BUMDes is running quite slowly so that it has not achieved the goal of establishing BUMDes, this can be proven by the many obstacles that occur. The factors are low community participation, support from the village government and lack of partner cooperation. The conclusion is that the management of BUMDes in Pangkalan Tampoi is not good enough, compared to BUMDes in Pelalawan Regency. Keywords: Management, Village-Owned Enterprises